Op zoek naar de perfecte match in vrijwilligersland - Els van Gilst; René Schalk; Henk Garretsen; Ien van de Goor (Journal of Social Intervention: Theory and Practice, 2015)
Finding the perfect volunteer matchOrganizations that are (partially) staffed by volunteers in the Netherlands are experiencing a growing need for volunteers. This relates to stricter laws and regulations, the changing deployment of volunteers and reforms in the care system (Bekkers & Boezeman, 2009; Devilee, 2005; MOVISIE, 2014; Rutte & Samsom, 2012).Volunteer centres can form part of the solution to the growing demand for volunteers. There are about 240 volunteer centres in the Netherlands. They promote volunteering and provide information, training, advice and support in this area. In addition, they play an active role as brokers in bringing together supply (volunteers) and demand (volunteer-involving organizations). This intermediary role is often the core business of volunteer centres (Ploegmakers, Merkus & Terpstra, 2011; Terpstra, Ploegmakers & van Laar, 2008).The success of volunteer brokerage remains relatively limited, however. Offline brokerage (at the office of the volunteer centre) is in about half of the cases successful. This falls to 37 percent for online brokerage. Volunteer brokerage is classed as successful when a volunteer is placed at an organization for a short-term project or a period of three months (Ploegmakers et al., 2011).Literature research (Van Gilst, Schalk, Garretsen & Van de Goor, 2011) was carried out to determine how the results of volunteer brokerage can be improved. The motivation and feelings of pride and respect on the part of a volunteer are found to be important for the level of satisfaction and willingness to keep on volunteering in both the short term and the long term.This article examines how success factors such as motivation, pride and respect can be incorporated into the daily brokerage practices of volunteer centres. Two research questions are central to this article:1. How does volunteer brokerage occur in practice?2. When and how can success factors for matching volunteers and organizations (partially) staffed by volunteers be incorporated into the practice of brokerage?The data are derived from a field study among volunteer centres, organizations (partially) staffed by volunteers and volunteers in the province of Zuid-Holland in the Netherlands. Three different research methods were used: survey, interviews, and desk research.The analysis of data from the field study showed that volunteer centres in the province of Zuid-Holland follow a similar procedure when it comes to matching volunteers. The brokerage procedure involves six phases. These phases may involve face-to-face contact with employees at the volunteer centre or online via the internet. Fully online brokerage with no personal contact was not an option at the time of the study. The six phases can be characterized as follows:• Orientation – Volunteers and organizations (partially) staffed by volunteers are given practical information about volunteering. Volunteers can search a database of volunteer jobs at the office or online. Usually, there is no database of volunteers for organizations to look into, because most volunteer centres do not have such databases.• Registration – In the case of online brokerage, a volunteer must register in order to access the contact details of organizations. With face-to-face brokerage, registration often is incorporated into the matching phase. An organization also has to register to make use of the service of the volunteer centre.• Matching – Information about a volunteer is collected at a face-to-face interview. This information may include prior education, skills, hobbies, interests, aspirations, feelings, motivation and ambitions. Occasionally, tests are used. Several tests are available to determine which volunteer job best suits the personality, motivation and interests of a particular volunteer. However, tests are often considered an unnecessary hindrance. The personal data, test results, and sometimes the intuition and personal impressions of employees of the volunteer centre are all used to select suitable vacancies. Matching on the internet is more restricted, and often remains limited to comparing vacancies. Organizations are checked in this phase. Research is done whether an organization is bona fide and whether the volunteer job vacancies that are offered, meet the criteria for volunteering.• Reaction – When a match is found, an interview is arranged between the volunteer and the organization.• Acquaintance – The volunteer and the volunteer organization get acquainted. The organization considers whether the volunteer is suitable for the vacancy. The volunteer receives more information about the organization and the job vacancy. Finally, a decision is made to accept or reject the volunteer.• Feedback – The organization and/or volunteer provide feedback on the outcome of the matching process. The role of the volunteer centre ends when a successful match has been established. If this does not occur, the whole procedure can be repeated.The description of the brokerage procedure makes it possible to pinpoint when and how success factors can be implemented in the daily practice of volunteer centres. The Matching Phase offers the best opportunity to influence the volunteer’s perception of an organization with a vacancy. This is important to address feelings of pride and respect. The volunteer centre evaluates and edits the text of the vacancy and explains the role to the volunteer face-to-face. During the AcquaintancePhase, information about the organization is also shared with the volunteer. This is the task of the organization itself, although volunteer centres may also play a supporting role. In all cases, good coordination between the volunteer centre and the organization is required to ensure that a consistent and appropriate image is presented.In terms of appraising the motives of a volunteer, the Matching Phase offers the greatest potential. In this phase, motives can thoroughly be considered during face-to-face contact with a prospective volunteer. Specific attention to motives in interview protocols is important. The use of tests or even the development of alternative tests should also be (re)considered. In the case of online brokerage, it is much harder to establish an accurate picture of motives. Online testing could offer a solution. However, interpretation possibilities are limited because test results cannot be supplemented with other information. This favours (for the time being) face-to-face contact during online Matching.In addition, the phase model of volunteer brokerage provides volunteer centres with a framework to describe their brokerage activities. This can be useful when training (new) employees and providing transparency for customers and funders.Op zoek naar de perfecte match in vrijwilligerslandDe vraag naar vrijwilligers neemt de laatste jaren sterk toe in Nederland. Dit heeft te maken met een strengere wet- en regelgeving, veranderende inzet van vrijwilligers en hervormingen in de zorg (Bekkers & Boezeman, 2009; Devilee, 2005; MOVISIE, 2014; Rutte & Samsom, 2012). Steunpunten vrijwilligerswerk kunnen als bemiddelaars bijdragen aan de regulering van de vraag naar vrijwilligers. De mate van succes van vrijwilligersbemiddeling is echter nog relatief beperkt. Uit literatuuronderzoek (Van Gilst et al., 2011) is bekend welke factoren bijdragen aan het succes van vrijwilligersbemiddeling. Dit artikel beschrijft de bemiddelingspraktijk van steunpunten vrijwilligerswerk en geeft aan wanneer en hoe de gevonden succesfactoren kunnen worden ingezet in deze bemiddelingspraktijk om het resultaat te verbeteren. De praktijkgegevens zijn afkomstig van een veldonderzoek onder steunpunten, vrijwilligers en organisaties die met vrijwilligers werken.